Level of habitual physical activity among 13-year-old adolescents from Spain and India. A cross-cultural study - López Sánchez, G.F.; Ahmed, Md. D.; Díaz Suárez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The level of physical activity of people is a very important issue internationally. The aim of this study was to analyze the level of habitual physical activity among adolescents from India and Spain. To achieve this purpose, the questionnaire Physician-based Assessment and Counseling for Exercise (PACE) was used. This questionnaire assesses with two questions how many days in the last week (PACE 1) and in a usual week (PACE 2) the subject does at least 60 min of physical activity. The study sample consisted of 154 13-year-old adolescents. Out of total sample, 61 adolescents (36 males, 59 %, and 25 females, 41%) were from Nagaon, Assam (India), and 93 adolescents (39 males, 42%, and 54 females, 58%) from the Region of Murcia (Spain). The results showed that the 13-year-old adolescents from Spain and India do not do enough physical activity, according to the recommendations of the WHO. The 80.5% of the Spanish adolescents and the 76% of the Indian adolescents of the sample were inactive considering the classification of PACE questionnaire. Therefore, intervention programs to increase the level of physical activity are suggested for both countries.